068 Evaluation of the long-term treatment effect of teriflunomide on cognitive outcomes and association with brain volume change: data from temso and its extension study. Issue 6 (24th May 2018) - Sprenger, Till; Lechner-Scott, Jeannette; Sormani, Maria P; Wolinsky, Jerry S; Wuerfel, Jens; Thangavelu, Karthinathan; Cavalier, Steven; Mandel, Matt; Kappos, Ludwig
Abstract : Introduction: In a blinded SIENA (Structural Image Evaluation using Normalisation of Atrophy) analysis of TEMSO (NCT00134563 ), teriflunomide significantly reduced brain volume loss (BVL) over 2 years vs placebo. Further analysis indicated a strong correlation between 2 year BVL and disability worsening, showing better disability outcomes for patients with lower rates of BVL. Here, we explore the relationship between BVL and long-term changes in cognitive function in TEMSO and its extension (NCT00803049 ). Methods: The effect of teriflunomide on cognitive function was assessed by change from baseline in Paced Auditory Serial Addition Test (PASAT)−3 scores in the TEMSO core (n=1086) and extension (n=740) studies. To evaluate change in PASAT-3 scores over 5 years, the TEMSO population was categorised into groups defined by percentage brain volume change from baseline to Year 2 (assessed by SIENA). Results: Adjusted mean changes from baseline to Week 96 in PASAT-3 raw/Z-scores were –0.265/–0.022 and 0.870/0.073 for placebo and teriflunomide 14 mg, respectively (difference vs placebo, p=0.0435 in both instances). Long-term improvements in PASAT-3 Z-scores were observed with teriflunomide 14 mg treatment: mean (SD) changes from baseline at Weeks 156 and 276 were 0.194 (0.634) and 0.200 (0.677), respectively. Mean (SD) units of change from baseline in raw PASAT-3 scores for teriflunomide 14 mg–treated patients at Weeks 156 and 276 were 2.36 (7.73) and 2.43 (8.24), respectively. In an association analysis, the group with least BVL from baseline to Year 2 demonstrated a significant improvement in PASAT-3 score with teriflunomide treatment over 5 years vs the group with most BVL. Conclusion: Teriflunomide significantly improved PASAT-3 performance vs placebo over 5 years in the TEMSO core and extension studies. Slower rates of BVL over 2 years correlated with better long-term PASAT-3 improvement. This study suggests that BVL earlier in the disease course predicts longer-term cognitive function. Study support: Sanofi.